Pendampingan Perhitungan Harga Pokok Produksi Terhadap Harga Jual Pada UMKM Kaos Baba Sablon - Aisyah, Aisyah; Nurjanah, Yayuk (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The cost of production is all direct and indirect costs incurred by the company for the production process so that the goods and services can be sold. Companies must calculate the cost of goods because it is very important for the company's financial reporting. The calculation of the cost of production is carried out before the company determines the selling price. The purpose of preparing this final assignment is to determine the calculation of the cost of production of t-shirts and goodiebags on Baba Sablon T-shirts and the calculations for determining the selling price using the company method and the full costing method. The results of this review show that the selling price made by the company is lower than the selling price after evaluation. According to the company, the selling price for t-shirt products is IDR 55,000/pcs and goodiebag products is IDR 8,000/pcs, while the selling price using the full costing method for t-shirt products is IDR 70,000/pcs and for goodiebag products is IDR 10,000/pcs, this is because the company does not charge indirect labor costs and factory overhead costs. Keywords: Cost Accounting, Cost of Goods Production, Selling Price